Metal mixture toxicity to aquatic biota in laboratory experiments: Application of the WHAM-FTOX model - Tipping, E.; Lofts, S. (Aquatic toxicology, 2013)
•Metal accumulation by living organisms is successfully simulated with WHAM.•Modelled organism-bound metal provides a measure of toxic exposure.•The toxic potency of individual bound metals is quantified by fitting toxicity data.•Eleven laboratory mixture toxicity data sets were parameterised.•Relatively little variability amongst individual test organisms is indicated. The WHAM-FTOX model describes the combined toxic effects of protons and metal cations towards aquatic organisms through the toxicity function (FTOX), a linear combination of the products of organism-bound cation and a toxic potency coefficient (αi) for each cation. Organism-bound, metabolically-active, cation is quantified by the proxy variable, amount bound by humic acid (HA), as predicted by the WHAM chemical speciation model. We compared published measured accumulations of metals by living organisms (bacteria, algae, invertebrates) in different solutions, with WHAM predictions of metal binding to humic acid in the same solutions. After adjustment for differences in binding site density, the predictions were in reasonable line with observations (for logarithmic variables, r2=0.89, root mean squared deviation=0.44), supporting the use of HA binding as a proxy. Calculated loadings of H+, Al, Cu, Zn, Cd, Pb and UO2 were used to fit observed toxic effects in 11 published mixture toxicity experiments involving bacteria, macrophytes, invertebrates and fish. Overall, WHAM-FTOX gave slightly better fits than a conventional additive model based on solution concentrations. From the derived values of αi, the toxicity of bound cations can tentatively be ranked in the order: H<Al<(Zn–Cu–Pb–UO2)<Cd. The WHAM-FTOX analysis indicates much narrower ranges of differences amongst individual organisms in metal toxicity tests than was previously thought. The model potentially provides a means to encapsulate knowledge contained within laboratory data, thereby permitting its application to field situations.